Reason and reform : how policy reforms have shaped India - Debroy, Bibek; Jhurani, Diwakar (New Delhi: Academic Foundation, 2021)
This book attempts to provide perspectives and lessons from some of the most crucial influences and incidents that have impacted Indian public policies. While the thrust is on post-colonial era, many prescriptions from India$1 (Bs centuries-old legacy of governance principles and policymaking are highlighted. The book covers a breadth of policy subjects in eight themes, from justice delivery to economic planning, institutional governance to infrastructure creation. Short chapters and easy-to-read prose will aid readers keen to grasp the uniquely Indian story spiced with its own share of policy reform experiments, some bitter, some sweet. And hopefully, the information, insights and ideas in this book can be used as tools to drive change by all those who have a stake in India. (3z(BA fearless examination of intractable questions and a powerful narrative that imposes order on something as chaotic as a nation$1 (Bs reform journey! Reason and Reform is a brilliant story of what brought India to where it is. The breadth of coverage is breathtaking; the authors tirelessly tease apart the first principles of reforms in domains as diverse as law and order, infrastructure, planning and the welfare state. Powerful, luminous, and full of charming anecdotes, this is a must-read for anyone curious about the Indian reform story and the learnings from the same.(3y (BKrishnamurthy Subramanian Chief Economic Advisor, Ministry of Finance, Government of Indias
English.
Keywords: Infrastructure (Economics) -- India; Economic policy -- 1947. -- Politics and government